Metagenomics Reveals Dominant Unusual Sulfur Oxidizers Inhabiting Active Hydrothermal Chimneys From the Southwest Indian Ridge - Wang, Yong; Bi, Hong-Yu; Chen, Hua-Guan; Zheng, Peng-Fei; Zhou, Ying-Li; Li, Jiang-Tao (Frontiers in Microbiology, 2022)
The deep-sea hydrothermal vents in the Southwest Indian Ridge (SWIR) are formed by specific geological settings. However, community structure and ecological function of the microbial inhabitants on sulfide chimneys of active hydrothermal vents remain largely unknown. In this study, our analyses of 16S rRNA gene amplicons and 16S rRNA metagenomic reads showed dominance of sulfur-oxidizing Ectothiorhodospiraceae, Thiomicrorhabdus, Sulfurimonas and Sulfurovum on the wall of two active hydrothermal chimneys. Compared with inactive hydrothermal sediments of SWIR, the active hydrothermal chimneys lacked sulfur-reducing bacteria. Metabolic potentials of the retrieved 82 MAGs suggest that sulfur oxidation might be conducted by Thiohalomonadales (classified as Ectothiorhodospiraceae based on 16S rRNA gene amplicons), Sulfurovaceae, Hyphomicrobiaceae, Thiotrichaceae, Thiomicrospiraceae, and Rhodobacteraceae. Calvin-Benson-Bassham and reductive TCA pathways were employed by these bacteria for CO2 fixation. In Thiohalomonadales MAGs, we revealed putative phytochrome, carotenoid precursor and squalene synthesis pathways, indicating a possible capacity of Thiohalomonadales in adaptation to dynamics redox conditions and in utilization of red light from the hot hydrothermal chimneys for photolithotrophic growth. This study therefore reveals unique microbiomes and their genomic features in the active hydrothermal chimneys of SWIR, which casts lights on ecosystem establishment and development in hydrothermal fields and deep biosphere.